The Ku Klux Klan and Ontario’s Evolving Britishness: A Case Study of Belleville and Hastings County - Parsons, Trevor (Ontario History)

(untitled) (The Ontario Historical Society, 2024)
This paper presents a microhistorical account of the Ku Klux Klan and its leader, George Marshall, in the Bay of Quinte region in the 1920s. It argues that the Klan and its opponents engaged in a largely non-violent war of words reflecting two competing visions of Ontario’s Britishness. The first being the Klan’s narrowly defined model of citizenship—one that was racialized, exclusive, and based on the superiority of Anglo-Saxon Protestantism. The second stood in opposition to the Klan and was comprised a loosely organized network advocating the mending of racial divides, religious tolerance, and a more open society. The activities of the Klan, and even those purporting to represent it, included violence and intimidation directed against Jews and Asians, but the mainstay of their vitriol was directed against Roman Catholics. This paper will add greater depth to and challenge the assertion that Ontario’s historical Britishness was monolithic; in fact it had multiple interrelated and competing strains providing the impetus for debates surrounding the province’s evolving identity during the 1920s.